Robust estimates in generalized partially linear models - Boente, G. (2006)
In this paper, we introduce a family of robust estimates for the parametric and nonparametric components under a generalized partially linear model, where the data are modeled by y i |(x i , t i ) ∼ F (·, μ i ) with μ i = H(η(t i ) + x i T β), with for some known distribution function F and link function H. It is shown that the estimates of β are root-n consistent and asymptotically normal. Through a Monte Carlo study, the performance of these estimators is compared with that of the classical ones. © Institute of Mathematical Statistics, 2006.